Synthesis And Characterization Of Phenyl Functionalized Magnetic Nanoparticles As Sorbent In Micro-Solid Phase Extraction Of Polycyclic Aromatic Hyrocarbons And Organophosphorus Pesticides - Hassan, Farah Wahidah Mohd (2018)
A phenyl-functionalized magnetic sorbent (PMS) was prepared and employed in the proposed microextraction methods for the analysis of selected polycyclic aromatic hydrocarbons (PAHs) and organophosphorus pesticides (OPPs) compounds. A vortex-assisted emulsification combined with salt-induced demulsification and magnetic dispersive micro-solid phase extraction (VAE-SID-MDMSPE) based on PMS was developed for the determination of selected PAHs compound namely, fluorene (FLU), anthracene (ANT), fluoranthene (FLA) and pyrene (PYR) in environmental water, sugarcane juice and tea samples.